The Effect of Health Education with the Buzz Group Method on Narcolema Bahavior in Adolescents - Dwi Maya Firdayanti; Ilmiatus Qoyimah; Miftahul Munir; Hanim Nur Faizah; Hanatasya Ridha Deanira; Nurus Syafaah (Indonesian Journal of Global Health Research, 2025)
Narcolema behavior is an activity to seeking satisfaction from sexual desires or urges that involve physical, mental and emotional using internet or computer media, this condition occurs because of curiosity about sexuality in adolescents.This study aims to determine the effect of health education with the buzz group method on narcolema behavior in class X adolescents at Senior High School Tuban Regency. The research design used in this study is Quantitative Pre-experimental : pre-post test (one group pre-post test design) with a cohort approach. The population in this study ware all class X adolescents of Senior High School 3 Tuban as many as 36 adolescents and Senior High School 1 Bancar as many as 35 adolescents with a total population of 71 adolescents selected by cluster random sampling technique obtained 30 adolescents from each school. The researcher will administer a pre-test (initial observation) before providing the treatment (x). After the treatment is given, a post-test (final observation) will be conducted. This procedure is carried out to determine the difference between the pre-test and post-test results. This study uses a cohort approach to collect data, so that the effect of health education using the Buzz Group method on narcolema behavior among adolescents at Senior High Schools in Tuban Regency can be determined.The results of the study conducted after being analyzed using the Wilcoxon test with a significance of α=<0.05 were proved to reduce narcolema behavior with a value of ρ = 0.000 <0.05 which means H₁ is accepted, namely there is an influence of health education with the buzz group method on narcolema behavior in class X adolescents . From the description above, it can be concluded that health education with the Buzz Group method affects narcolema behavior in class X adolescents at Senior High School Tuban Regency.